Radio Communication for the Dissemination of Improved Livestock Production Technologies in Ethiopia - Zeleke, Muluken; Wamatu, Jane; Abiso, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The ICARDA pilot radio project, launched in 2023, aimed to address knowledge gaps among smallholder farmers in Ethiopia by providing structured and contextually tailored content on livestock management, specifically focusing on sheep fattening. Leveraging the wide reach of mass communication via radio, the project aimed to broadcast programs promoting improved livestock production technologies in five local languages across culturally diverse regions in Central Ethiopia, thus ensuring improved comprehension and outreach to rural and marginalized populations who may not speak or understand dominant languages. A mid-term evaluation revealed that despite increased knowledge and higher mid-term household incomes - 4.7 times the baseline - the economic impact on livestock ownership was minimal due to short-term constraints and barriers to social learning. Challenges such as lack of working capital and space for rearing livestock hindered youth and women from adopting technologies; thus, knowledge-sharing declined by 8%.